Immunomodulatory properties of extracellular vesicles in the dialogue between placental and immune cells. (27th December 2020) - Favaro, Rodolfo R.; Murrieta‐Coxca, Jose Martín; Gutiérrez‐Samudio, Ruby N.; Morales‐Prieto, Diana M.; Markert, Udo R.
Abstract: Extracellular vesicle (EV)‐mediated communication has been implicated in the cooperative alliance between trophoblast and immune cells toward maternal tolerance and placentation. Syncytiotrophoblast cells secrete EVs directly into the maternal circulation, which are taken up by immune cells, endothelial cells, and other cell types. Initial evidence also shows that EVs produced by immune cells are, in turn, incorporated by trophoblast cells and modulate placental responses. Non‐coding RNAs (ncRNAs), proteins, and lipid mediators transported in EVs are able to influence proliferation, differentiation, cytokine production, and immunological responses of recipient cells. The molecular alphabet and cellular targets involved in this dialogue are being revealed. Nevertheless, several questions regarding the whole content, surface markers, and biological functions of EVs still remain to be investigated in both physiological and pathological conditions. Analysis of circulating EVs in maternal blood has the potential to serve as a minimally invasive approach to monitoring placental functions and immunological features of pregnancy, aiding in the diagnostics of complications. This review addresses the immunomodulatory properties of EVs and their tasks in the communication between placental and immune cells.